Cloning and Expression of the Xylanase Gene From Bacillus Coagulans and the M Gene of Newcastle Disease Virus in Lactococcus Lactis - Chang, Li Yen (2001)
Lactococcus lactis is being developed as a vaccine delivery system as it bears no threat to animal and human health. It has been used for centuries in the fermentation of foods and is generally recognised as safe. However, a safety factor pertaining to the type of selectable marker present on the vector system poses to be of concern. Chances of the transfer of antibiotic resistance genes, usually employed by vectors as selectable markers, into the natural environment become a possible risk. Therefore, there is a need for the development of ideal vectors without such selectable markers (Dertzbaugh, 1998). The activity of the xylanase gene of Bacillus coagulans ST -6 can be detected on Remazol Brilliant Blue-Xylan (RBB-Xylan) as a clear halo zone against a dark blue background. This characteristic allows xylanase to be used as a selectable chromogenic marker on any vector system. On the other hand, the matrix or membrane (M) protein of Newcastle disease virus (NDV) strain AF 2240 can be useful as an antigen to generate antibody response towards NDV infection in chickens.Both, the xylanase gene (0.8 kb) of B. coagulans ST-6 and the M gene (1.1 kb) of NDV strain AF 2240 were cloned in lactococcal expression vector pMG36e and transformed into Escherichia coli XLI-blue MRF'. The recombinant plasmids, pMG36e-X and pMG36e-X-M were sub-cloned into L. lactis MG 1363 via electroporation. The insertion and orientation of the xylanase gene was confmned using restriction enzyme analysis and PCR amplification. Xylanase activity and expression on RBB-Xylan agar plates further confmned its presence in the recombinant plasmid pMG36e-X. In addition, the enzyme activity was also quantitatively showed using the Somogyi-Nelson assay. The sequence of the M gene obtained in clone pMG36e-X-M from L. lactis MG 1363 was found to be 99% homologous to the established sequence (Jemain, 1999). Expression of the fusion M protein was studied at the transcriptional leve1. RT -PCR was used to detect the transcription of the gene using RNA of L. lactis MG1363 containing the recombinant plasmid pMG36e-X-M as template. The size of the RT-PCR product correlated with the size of the cloned M gene (1.1 kb). In addition, the RT-PCR product was sequenced to confirm the presence of the M gene. Based on the results obtained, recombinant plasmids pMG36e-X and pMG36e-X-M were successfully constructed and introduced into E. coli XLI-blue-MRF' and L. lactis MG1363. The recombinant DNA pMG36e-X is capable of expressing the xylanase gene and can be further developed as a chromogenic selection marker for a new and improved food-grade shuttle vector for E. coli and L. lactis. On the other hand, expression of the fusion M gene was detected at transcriptional level in recombinant clone pMG36e-X-M.